2021
DOI: 10.3390/en14175559
|View full text |Cite
|
Sign up to set email alerts
|

Experimental Research on the Macroscopic and Microscopic Spray Characteristics of Diesel-PODE3-4 Blends

Abstract: Polyoxymethylene dimethyl ether (PODE) is a low-viscosity oxygenated fuel that can improve the volatility of blended fuels. In this work, the macroscopic and microscopic spray characteristics of diesel-PODE3-4 under different ambient temperatures and injection pressures (IP) are studied. The studied blends consisted of pure diesel (P0), two diesel blend fuels of 20% (P20) and 50% (P50) by volume fraction of PODE3-4. The Mie scattering and Schlieren imaging techniques are used in the experiment. The results sho… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(3 citation statements)
references
References 49 publications
0
3
0
Order By: Relevance
“…While surface tension affects the fuel surface area, volatility influences the spray evolution and mixture formation [114,[156][157][158][159]. High volatile fuel tends to increase the evaporation rate and lowers SMD thus reducing the spray penetration length [160][161][162][163][164][165]. Low volatile fuel, on the other hand, has relatively lower evaporation rate, larger droplets size, thus increasing spray penetration length, which in some cases could lead to the wall impingement [166][167][168][169][170].…”
Section: Factors Affecting Spray Evolutionmentioning
confidence: 99%
“…While surface tension affects the fuel surface area, volatility influences the spray evolution and mixture formation [114,[156][157][158][159]. High volatile fuel tends to increase the evaporation rate and lowers SMD thus reducing the spray penetration length [160][161][162][163][164][165]. Low volatile fuel, on the other hand, has relatively lower evaporation rate, larger droplets size, thus increasing spray penetration length, which in some cases could lead to the wall impingement [166][167][168][169][170].…”
Section: Factors Affecting Spray Evolutionmentioning
confidence: 99%
“…Using renewable, low carbon non-fossil based fuels for ICE applications is a promising option to reduce pollutant emissions and carbon footprint [3,4]. Several studies showed the potential of these fuels to achieve emission reduction objectives in different facilities, such as engines [5][6][7][8] and optical vessels [9,10]. Among these fuels, oxymethylene dimethyl ethers (OME n ) are attractive due to their physicochemical properties [11].…”
Section: Introductionmentioning
confidence: 99%
“…Zhao et al [23] investigated two neighboring droplets at We = 12.3 in the bag-breakup regime with the normalized separation distance S less than 3, and they found a coalescence mode at S < 1.3 and a puncture mode at the higher S of the two tandem droplets. Chen et al [24] discovered the effect of ambient temperature and injection pressure on the spray atomization of diesel and diesel-polyoxymethylene dimethyl ether (PODE 3-4 ) at 20 and 50% fractions of the volume. The results showed that with the increase of temperature and injection pressure, the droplet size and SMD of diesel and diesel-PODE 3-4 decreased.…”
Section: Introductionmentioning
confidence: 99%